FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BUANG AIR BESAR DI JAMBAN DI DESA GUNUNGSARI KECAMATAN PULOSARI KABUPATEN PEMALANG - Amalinda Kris Wijayanti; Laksmono Widagdo; Zahroh Shaluhiyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Behavior of using toilet is the most effective, simple, and easy to prevent several kind of disease such as diarrhea, cholera. Pemalang cases of diarrhea in the year 2012 as many as 55.014 unreported cases. The number of cases has increased compared to the year 2011 as many as 11.982 cases. Based on data obtained in the village Gunungsari Pulosari the District Pemalang district that the head of the family who defecation as many as 224 households.Extension healthy latrines as a solution by the Health Department program through methods STBM (Community Based Total Sanitation ) first pillar is Stop Babs. The purpose of this study is to determine the factors associated with bowel movements in the toilet. This type of research is quantitative , using analytic study that examined the relationship between independent variables and the dependent variable, with cross sectional design, study population consisted of 100 head of households. Data analyzed is using univariate and bivariate, analytic bivariate test Chi- Square (µ = 0.05). Significance is determined if the p-value less than 0.05.The findings showed that of the 100, 57 % aged ≥ 42 years, 77 % had a job, 53 % have an income < UMR, 61 % had good knowledge, 73 % have a good attitude, 57 % have good manners, 64 % availability of the category of good, 65 % have a good family support, 69 % had good support health workers, 74 % have a good peer support, 57 % have a good support community leaders. Of the Chi - Square test showed that the variable)job ( p - value = 0.002 ), the level of knowledge ( p - value = 0.002 ) , attitude ( p - value = 0.019) , the availability of means ( p- value = 0.000 ) , family support ( p - value = 0.005) , the support of community leaders ( p - value = 0.040 ) have a relationship significantly with defecation in the toilet. It is suggested to local governments to coordinate with relevant agencies to engage with the community try to get people to defecate in toilet.